1996
DOI: 10.1089/hum.1996.7.16-1955
|View full text |Cite
|
Sign up to set email alerts
|

Limited Antitumor T Cell Response in Melanoma Patients Vaccinated with Interleukin-2 Gene-Transduced Allogeneic Melanoma Cells

Abstract: We have immunized advanced melanoma patients with a HLA-A2-compatible human melanoma line genetically modified to release interleukin-2 (IL-2), to elicit or increase a T cell-mediated anti-melanoma response that may affect distant lesions. Twelve stage-IV patients were injected subcutaneously at days 1, 13, 26, and 55 with IL-2 gene-transduced and irradiated melanoma cells at doses of 5 or 15 x 10(7) cells. Both local and systemic toxicities were mild, consisting of transient erythema at the vaccination site; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 24 publications
(17 reference statements)
0
28
0
Order By: Relevance
“…However, early reports of allogeneic vaccines modified to secrete IL-2 have reported a limited response. 20,21 As pre-clinical models for autologous vaccines show GM-CSF to be more potent than IL-2, it would seem logical to expect that this may also extend to allogeneic vaccines. A recent report 22 showed that GM-CSF enhanced the protective ability of autologous tumour vaccine cells modified to express an allogeneic MHC.…”
Section: Introductionmentioning
confidence: 99%
“…However, early reports of allogeneic vaccines modified to secrete IL-2 have reported a limited response. 20,21 As pre-clinical models for autologous vaccines show GM-CSF to be more potent than IL-2, it would seem logical to expect that this may also extend to allogeneic vaccines. A recent report 22 showed that GM-CSF enhanced the protective ability of autologous tumour vaccine cells modified to express an allogeneic MHC.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 In addition, a peptide vaccine is limited to the range of the population that carry the corresponding MHC restriction element. Genetically modified whole cell tumor vaccines (such as cytokine-gene transduced autologous cells), [8][9][10] have the disadvantage of introducing a lot of potential irrelevant antigenic material which might cause unspecific and adverse effects, together with the complication of requiring large numbers of individual tumor cells.…”
Section: Iu Of Sfv/enh-p1a (Squares) or Sfv-p1a (Black Diamonds) Ormentioning
confidence: 99%
“…The most widely used vaccines in clinical studies are whole tumor cells either alone or in combination with B7 or cytokine genes. [8][9][10] More recent approaches include vaccination with peptide, recombinant viral and bacterial nucleic acid, heat-shock proteins or dendritic cells (DC). 1,2 However, there is presently no consensus on which of these different vaccine types are optimal for tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 The efficacy of vaccination on the generation of immune response is evaluated by comparing immunologic parameters before and after treatment; however, which of such parameters correlates with clinical response remains undetermined. 16 We and others have shown that the induction of antitumor CTL does not correlate with tumor regression in both humans [17][18][19] and mice. 15,20 The present study corroborates this conclusion and shows that activation of CD8 cells is necessary but not sufficient to induce the eradication of lung metastases.…”
Section: Discussionmentioning
confidence: 99%